Do social cognitive factors influence final-year undergraduate students’ intentions to pursue advanced degrees? An examination of the moderating effect of sex - Bayon, Chembelyn; Abejo, Maximino; Guinocor, Marvin; Garciano, Martha Joyce; Literatus, Jonita; Reveche, Shaleen Jean; Nudalo, Arnel; Gonzaga, Maria Cristina; Caminos, Israeli; Caminos, Roger; Borres, Vincent; Cortes, Sylvester (Frontiers in Education, 2024)
This study examines the factors influencing final -year undergraduate students' intention to pursue advanced degree within the lens of Bandura's (1986) Social Cognitive Theory (SCT). In addition, it investigates the moderating effect of sex to the causal paths in the proposed model. Using a quantitative cross-sectional survey design, 578 final-year undergraduate students from different degree programs participated in an online survey. The results revealed that outcomes expectation and social support are predictors of intention and intention is a predictor of implementation intention to pursue advanced degree. Meanwhile, self-efficacy does not influence intention, and sex does not moderate the hypothesized paths in the model. The findings suggest that SCT is useful and a robust framework to explain what influences undergraduate students' intention to pursue advanced degree as evidenced by high explanatory power of the structural model. Practical and theoretical implications are suggested along with implications for future research.